Fragmented fiber pollution from common textile materials and structures during laundry. Issue 13 (July 2022) - Palacios-Marín, Alma V; Jabbar, Abdul; Tausif, Muhammad
The fiber damage during manufacture, use, and service of textiles leads to fragmented fiber generation. All textiles (natural, regenerated, and synthetic polymer sources) release fiber fragments. Several textile structural parameters have been studied in association with fragmented fiber release; however, there is a paucity of work on the effect of different fiber types and yarn structures on fragmented fiber release. This study elucidates the impact of key fiber types and yarn structures (rudimentary elements of textiles) on fragmented fiber release during laundry. Five different bespoke textile samples from three primary yarn structures (flat filament, textured filament, and staple yarn) from the two most employed fibers (polyethylene terephthalate and cotton) were subjected to repeated simulated washing processes to quantify shed fragmented fiber and length distribution of the collected fragmented fiber. The results show that yarn structure impacts the quantity of fragmented fiber shed and the length distribution profile. The release of fragmented fiber decreases during repeated washing of fabrics from staple and textured filament yarns, except for fabrics from flat filament yarns. The mean fragmented fiber length for all samples increases on repeated laundering. The quantity of fragmented fiber shed per gram of textile, and the length distribution profile of fragmented fiber from the woven fabrics made of the five types of yarns after the first and fifth washing cycles were estimated.